Construindo comunidades virtuais e reputação digital a partir de conteúdo e relacionamento no LinkedIn - Silvestre Junior, Paulo Fernando (2020)
Social networks play a central and growing role in people's lives, especially since the launch of the iPhone in 2007, which made smartphones popular, making us people permanently connected to all types of information. Brazilians occupy a prominent place in the use of networks: we are the second country in the world in terms of time on these platforms. The combination of smartphones and social networks has created a new way of communicating with their audience for professionals and companies, based on the publication of content on social networks. Today it is unimaginable to think about starting a marketing program without it. However, what is seen is that the vast majority of companies and professionals do not get all the results they could from this initiative, due to a lack of understanding of what good content and good relationships are. In short, they make a lot of "noise" in the networks, but build little reputation. In this scenario, LinkedIn stands out as a social network where users seek information and contacts that allow them to grow personally and professionally, instead of other content, more common on other social networks. To reinforce such purpose, since 2016, the platform publishes a list of users called Top Voices, precisely those who, according to LinkedIn itself, produce high quality content and build efficient relationships with other users. In Brazil, where there are 41 million active LinkedIn users, there are only 60 Top Voices, including the author of this study. Motivated by his personal experience, the present study proposes to identify good practices for the relationship between professionals and companies with their audience based on their publications. Extensive fieldwork was carried out, with analysis of 966 publications of 60 relevant users and interviews with these people and editors from LinkedIn itself. Thanks to that, it answers how digital social networks, and LinkedIn in particular, can effectively allow people to create a solid reputation from the production of content and relationships with other users, if it is possible to transpose the reputation built on the network beyond it, and what are the most efficient mechanisms for building such a reputation. Although the study does not propose to be a “guide of how to publish on digital networks”, it does offer resources for anyone wishing to produce high-level discussions online